Abortion law and its reform in Malaysia / Norhayati Mohd. Darus - Mohd. Darus, Norhayati (Faculty of Law, 1983)
Abortion is a topic that involves legal, medical, moral as well as social questions. But we are really concern with legal reform. To what extent is it possible to bring about legal reform depends on whether the legalization is medically viable, religiously sound or morally and socially acceptable. The legal reform involves the position of the present laws regarding abortion in Malaysia. How far is the law adequate in helping the women? Does the law recognise that it is the right of the woman to abort or there is no right at all being recognized The medical reform raises the question as to whether the legalization of abortion would affect the woman's physical or mental health.